Towards a Nuclear-Weapon-Free World: How Can the World Resolve the Disharmony Between the UNSC and UNGA? - Nakanishi, Hiroaki (Victoria University of Wellington Law Review, 2012)
Global momentum towards a "Nuclear-Weapon-Free World" (NWFW) has been growing since the end of the Cold War. Nevertheless, in the international community, it is still difficult to discern a unified voice about how to approach a NWFW, utilising international law. This is possibly because of ongoing disagreement between nuclear weapon States (NWS) and non-nuclear weapon States (NNWS), particularly the non-aligned countries. The issue revolves around the understanding of the Nuclear Non-Proliferation Treaty (NPT), especially art 6 of that treaty which sets out the contracting parties’ nuclear disarmament obligations. Reflecting the discord between the NWS and NNWS, this article sheds light on the gap between the United Nations Security Council (UNSC) and the United Nations General Assembly (UNGA)’s perceptions of, and actions taken towards, the realisation of a NWFW. The article calls for the minimisation of disharmony by reinvestigating the roles of the United Nations system and the NPT in establishing a NWFW, and through observing the UNGA’s current position.